Unseen and unheard: the invisibility of kelp forests in international environmental governance - Valckenaere, Jurgen; Techera, Erika; Filbee-Dexter, Karen; Wernberg, Thomas (Frontiers in Marine Science, 2023)
•Kelp forests are one of the most extensive coastal ecosystems in the world. They serve a myriad of ecological functions, support substantial biodiversity, and contribute to a multitude of services essential to our contemporary society. Unfortunately, they declining. •International governance regimes and institutions play an important role in addressing threats to marine ecosystems and combatting declines. However, not all ecosystems receive the same level of global governance attention. •There is a growing interest in coastal ecosystems, and an overall increase in conservation targets and restoration programmes on many international platforms. We demonstrate that kelp forests consistently receive the least global governance attention compared to other dominant marine habitats. •To address the disconnect between kelp science and environmental governance, we make five recommendations for the future.